2018
DOI: 10.20524/aog.2018.0273
|View full text |Cite
|
Sign up to set email alerts
|

Differences in dietary habits between patients with inflammatory bowel disease in clinical remission and a healthy population

Abstract: Background:Although patients with active inflammatory bowel disease (IBD) change their dietary habits according to suggestions from their healthcare team, no restriction is required in the remission phase. Accordingly, we compared eating patterns in IBD patients with drug-induced clinical remission with those in healthy subjects.Methods:A total of 150 IBD patients, 84 with Crohn’s disease (CD) and 66 with ulcerative colitis (UC), in clinical remission, receiving immunomodulator/biologic therapy, and 100 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 29 publications
3
48
1
Order By: Relevance
“…Regarding the intake of dietary fiber, expressed as both the total and grams per 1000 kcal/day, we observed reduced values (7.2 g/1000 kcal) compared to the LARN recommendation (RI = ~ 15 g/1000 kcal), even in patients in clinical remission. Previous studies showed an average daily intake of fiber/1000 kcal that ranged from 6.13 [31] to 11.1 g [20], without showing any differences between active and quiescent groups [21], in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the intake of dietary fiber, expressed as both the total and grams per 1000 kcal/day, we observed reduced values (7.2 g/1000 kcal) compared to the LARN recommendation (RI = ~ 15 g/1000 kcal), even in patients in clinical remission. Previous studies showed an average daily intake of fiber/1000 kcal that ranged from 6.13 [31] to 11.1 g [20], without showing any differences between active and quiescent groups [21], in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the representative sample, dietary MUFA intake from foods like olive and canola oils, avocado, and nuts were low in patients with CD. One recently published study showed that dietary lipid and overall energy intake in a mixed IBD sample was higher than that of the healthy control subjects, however, no differences were observed in protein and carbohydrate intake [ 34 ]. Dietary lipid composition, unfortunately, was not reported in this study, rendering the proportion of MUFA and PUFA unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The fiber intake (g) was assessed as an additional variable that may influence the other factors [31], because even individuals in the remission phase may reduce their fiber intake due to the fear of disease complications [32]. This variable was assessed using the Polish dietician software Dieta version 5.0 (National Food and Nutrition Institute, Warsaw, Poland) and the Polish database of the nutritional value of the products [33].…”
Section: Methodsmentioning
confidence: 99%